'Embraced in the Fathomless Love': Bodily Aspects of Mystical Enjoyment in the Work of John of Ruusbroec. Issue 1 (4th August 2014) - Faesen, Rob
Abstract : Christian mystical literature contains many descriptions of a very corporeal nature at crucial moments. John of Ruusbroec addressed this issue several times. He considers this a matter that is fundamentally human, and one that affects both men and women. In Ruusbroec's conception, the contact with God is not only 'above' or 'outside' the human person, but is also in the human person, since this contact occurs on the level of being itself. He underscores that God — the source of being — is also fundamentally relational, namely the relationship between the Father and the Son in the loving unity of the Holy Spirit. This union of love is the greatest possible bliss. Experiences felt on the most fundamental level of being have an effect on the whole person, including the body. However, historically we see the emergence of a different conception of human being. Then, indwelling is no longer understood, and as a result the reality of the body and the bodily aspects of the union with God are reinterpreted.